Synthesis of BSCF perovskites using a microwave-assisted combustion method. Issue 3 (15th February 2016) - Nuernberg, R.B.; Morelli, M.R.
Abstract: Ba0.5 Sr0.5 Co0.8 Fe0.2 O3− Δ (BSCF) perovskite-type oxide was synthesized using a microwave-assisted combustion method. Following about 10 min of exposure to microwave, the combustion reaction was self-ignited and it produced a porous powder. For comparison, BSCF perovskite powders were also synthesized by conventional heating. Two different fuel types were used in the two heating methods. The crystalline BSCF powders were characterized using scanning calorimetry and thermogravimetry (DSC/TG), X-ray diffraction (XRD), BET surface area measurement, scanning electron microscopy (SEM), and dilatometric analysis. The microwave heating method resulted in a powder with nanometric crystallites, submicrometric particles, and a specific surface area of 9.93 m 2 /g, which corresponds to a BET diameter of approximately 100 nm. The dilatometric analysis showed that the microwave-synthesized BSCF powder has the maximum sintering rate at 970 °C, but the sintering process initiates at lower temperatures. Highlights: BSCF powders were successfully synthesized by microwave-assisted combustion method. Microwave heating has resulted in BSCF powder with a better set of characteristics. Urea is a very efficient fuel in combustion synthesis of BSCF phase. The powder synthetized with microwave heating show a lower sintering temperature.